1988
DOI: 10.1152/ajpregu.1988.254.6.r863
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of prostaglandin E2, cAMP, and vasopressin in lithium-induced polyuria

Abstract: The involvement of prostaglandin E2 (PGE2), adenosine 3',5'-cyclic monophosphate (cAMP), and vasopressin in lithium-induced polyuria was investigated in rats. Administration of LiCl (4 mmol/kg body wt) for 7 days induced a marked polyuria with a significant excretion of urinary PGE2. Administration of indomethacin (IND, 5 mg/kg body wt) for 4 days to lithium-induced diabetes insipidus (LiDI) rats diminished urine volume by 80% and urinary PGE2 by 85%. The in vitro data of the intact rat kidney showed that lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 0 publications
4
36
0
1
Order By: Relevance
“…It has been suggested that lithium acts by inhibiting adenylate cyclase activity in the collecting duct principal cells (2,5), thus preventing the production of cAMP, the second messenger for vasopressin. Prostaglandins may (6) or may not (7) play a part in this inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that lithium acts by inhibiting adenylate cyclase activity in the collecting duct principal cells (2,5), thus preventing the production of cAMP, the second messenger for vasopressin. Prostaglandins may (6) or may not (7) play a part in this inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Not only has vasopressin been shown to stimulate prostaglandin synthesis in both collecting duct and interstitial cells, but renal prostaglandin synthesis is also increased in a variety of pathological conditions as well as during periods of dehydration (6,20,33,36). The production of prostaglandins in response to vasopressin may represent a negative feedback mechanism, since the major effect of prostaglandins on fluid balance appears to be mediated by the binding of PGE 2 to the EP 3 receptor, subsequently inhibiting increased intracellular cAMP, thereby hindering vasopressin mediated AQP2 shuttling (17,27).…”
mentioning
confidence: 99%
“…In animal models, Li-induced polyuria is associated with decreased protein abundance of AVP-regulated collecting duct water channel aquaporin (AQP)2 (31,36). The AVP resistance in Li-induced NDI has been attributed to increased production of renal prostaglandin (PG)E 2 (48). PGE 2 is a potent antagonist of AVP action on collecting duct (19,40,44,56).…”
mentioning
confidence: 99%